2022
DOI: 10.1007/s13311-022-01193-z
|View full text |Cite
|
Sign up to set email alerts
|

Culture, Ethnicity, and Level of Education in Alzheimer's Disease

Abstract: Alzheimer’s disease (AD) is the most frequent cause of dementia, where the abnormal accumulation of beta-amyloid (Aβ) and tau lead to neurodegeneration as well as loss of cognitive, behavioral, and functional abilities. The present review analyzes AD from a cross-cultural neuropsychological perspective, looking at differences in culture-associated variables, neuropsychological test performance and biomarkers across ethnic and racial groups. Studies have found significant effects of culture, preferred language,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(46 citation statements)
references
References 169 publications
1
31
0
Order By: Relevance
“…Future studies should compare the diagnostic properties between patients with high-and low-education levels. Third, cognitive reserve was not specifically evaluated, although previous studies have reported years of education as a proxy for cognitive reserve ( Nicolas et al, 2020 ; Rosselli et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Future studies should compare the diagnostic properties between patients with high-and low-education levels. Third, cognitive reserve was not specifically evaluated, although previous studies have reported years of education as a proxy for cognitive reserve ( Nicolas et al, 2020 ; Rosselli et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…The study of culture and its meaning in neuropsychological assessment has focused on the description of different variables correlated with culture, such as patterns of ability, familiarity, cultural value, acculturation, and language ( Ardila, 2007 ; Rosselli et al, 2022 ). In this regard, education, which is strongly associated with patterns of ability, and language are especially important during the cognitive assessment.…”
Section: Introductionmentioning
confidence: 99%
“…It is not unusual that well educated people outperform their lower-educated peers, as cognitive tests often score abilities they are trained in. It is also remarkable that this fact is not necessarily related to the ability to solve everyday problems ( Rosselli et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, we found a positive correlation between educational level and executive function as seen in other studies. 23 , 24 Because the purpose of the present study was not to investigate whether education level acts as a factor in mediating WMH via executive function, education level was adjusted in the mediation analysis as a covariate.…”
Section: Discussionmentioning
confidence: 99%